In Vitro Antimicrobial Effects of Endoseal MTA and AH Plus Sealers on Enterococcus Faecalis and Candida Albicans Mature Biofilms - Elham Khoshbin; Forough Nikzad; Mohammad Reza Arabestani; Maryam Farhdian; Hamed Karkehabadi (Frontiers in Dentistry)
Objectives: This study compared the antimicrobial effects of Endoseal MTA and AH Plus sealers on Enterococcus faecalis (E. faecalis) and Candida albicans (C. albicans) mature biofilms on dentin blocks.